2013
DOI: 10.1105/tpc.113.118521
|View full text |Cite
|
Sign up to set email alerts
|

Sufficient Amounts of Functional HOP2/MND1 Complex Promote Interhomolog DNA Repair but Are Dispensable for Intersister DNA Repair during Meiosis in Arabidopsis  

Abstract: During meiosis, homologous recombination (HR) is essential to repair programmed DNA double-strand breaks (DSBs), and a dedicated protein machinery ensures that the homologous chromosome is favored over the nearby sister chromatid as a repair template. The HOMOLOGOUS-PAIRING PROTEIN2/MEIOTIC NUCLEAR DIVISION PROTEIN1 (HOP2/MND1) protein complex has been identified as a crucial factor of meiotic HR in Arabidopsis thaliana, since loss of either MND1 or HOP2 results in failure of DNA repair. We isolated two mutant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
80
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(90 citation statements)
references
References 98 publications
(157 reference statements)
10
80
0
Order By: Relevance
“…Thus, the quantity of functional MS5 c might not meet the threshold for normal male meiosis in MS5 b MS5 c , while the quantity of functional MS5 a far exceeds its minimal requirement. A recent example of similar dose-limiting effect in meiosis is the HOP2/MND1 complex, which promotes interhomolog DNA repair by stimulating DMC1 activity in a dosage-sensitive manner (Uanschou et al, 2013). Interestingly, in this study, we also observed that male meiosis is completely disrupted in MS5 b MS5 c , while the female meiosis largely proceeds normally.…”
Section: Differences In Fertility Mediated By Different Ms5 Alleles Msupporting
confidence: 68%
“…Thus, the quantity of functional MS5 c might not meet the threshold for normal male meiosis in MS5 b MS5 c , while the quantity of functional MS5 a far exceeds its minimal requirement. A recent example of similar dose-limiting effect in meiosis is the HOP2/MND1 complex, which promotes interhomolog DNA repair by stimulating DMC1 activity in a dosage-sensitive manner (Uanschou et al, 2013). Interestingly, in this study, we also observed that male meiosis is completely disrupted in MS5 b MS5 c , while the female meiosis largely proceeds normally.…”
Section: Differences In Fertility Mediated By Different Ms5 Alleles Msupporting
confidence: 68%
“…In addition, the interaction of HOP2/MND1 complex would be activated during the DMC1 pathway (Petukhova et al, 2005; Vignard et al, 2007), to enhance single-stranded DNA invasion (Chi et al, 2007), and thus the accumulation of DMC1 was effected by the expression of either protein (Vignard et al, 2007; Uanschou et al, 2013). Moreover, RAD54 as an accessory factor, could interact with RAD51 and DMC1 (Raschle et al, 2004), and RPA as a heterotrimeric single stranded DNA-binding protein implicated in meiotic recombination (Soustelle et al, 2002; Osman et al, 2011), modulating the assembly of RAD51 and DMC1 filaments in ssDNA during meiotic DSBs repairing (Osman et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…One report suggested that Arabidopsis Mnd1 is capable of enhancing Rad51-mediated IS repair in a Dmc1 2/2 mutant (Vignard et al 2007), but a more recent and extensive study came to the opposite conclusion (Uanschou et al 2013). Similarly, there are conflicting reports concerning the radiation sensitivity of somatic cells in Mnd1 2/2 mutants (Domenichini et al 2006;Kerzendorfer et al 2006).…”
Section: Hop2 -Mnd1mentioning
confidence: 90%